1998
DOI: 10.1111/j.1471-0528.1998.tb10054.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intra‐observer variation in the histopathological reporting of cervical squamous in traepithelial lesion susing a modified Bethesda grading system

Abstract: Objective 1. To assess inter-and intra-observer variation in the histopathological reporting of cervical colposcopic biopsies using a histologic modification of the cytological Bethesda grading system; 2. to determine the histologic profile of those cases which resulted in diagnostic disagreement.Methods Consecutive cervical colposcopic biopsies (n = 125) were assessed independently by six experienced histopathologists. Cases were classified as normal, low grade squamous intraepithelial lesion or high grade sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 13 publications
(12 reference statements)
3
75
0
1
Order By: Relevance
“…16,20 Numbers do not add up to totals due to missing data and are as shown. Cases of invasive cervical cancer are not included.-2 v 2 test for trend except for median RLU value that is by Kruskall-Wallace test.-3 P0 is ''warrants colposcopy'' diagnosis.- 4 If high-risk HPV DNA positive by hc2, RLU is relative light units that is an indicator of HPV DNA content or viral load. In our study, we observed good correlation between p16 INK4A immunohistochemical staining and a consensus pathological diagnosis of CIN 2,31, consistent with what has been shown previously in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,20 Numbers do not add up to totals due to missing data and are as shown. Cases of invasive cervical cancer are not included.-2 v 2 test for trend except for median RLU value that is by Kruskall-Wallace test.-3 P0 is ''warrants colposcopy'' diagnosis.- 4 If high-risk HPV DNA positive by hc2, RLU is relative light units that is an indicator of HPV DNA content or viral load. In our study, we observed good correlation between p16 INK4A immunohistochemical staining and a consensus pathological diagnosis of CIN 2,31, consistent with what has been shown previously in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…3 This results in marked difficulties in separating normal biopsies from CIN 1 and in distinguishing between CIN 1 and CIN 2,3 based on histopathology alone. 4 Recognition of this variability has led to concerted efforts to identify novel biomarkers capable of more reproducibly distinguishing between normal and CIN lesions and in reducing the variability in grading of CIN lesions. A number of potentially diagnostically useful biomarkers have been identified using conventional immunohistochemical approaches and tissue microarrays.…”
Section: Abstract: Cervical Intraepithelial Neoplasia; P16 Immunohismentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, classification agreement with lower variability between observers can be improved in a 2-tiered versus a 3-tiered system [10,28,[78][79][80][81][82][83][84][85][86][87]. Improved agreement among pathologists leads to a more consistent and reproducible diagnosis, which may lead to more valid clinical outcome data.…”
Section: Wg2 Recommendation Nomentioning
confidence: 99%
“…15,16 In women with abnormal smears, histological analysis of biopsy samples is used to establish the definitive diagnosis of the underlying lesion. However, as for cytology, histology is also affected by a substantial rate of interobserver discrepancies even among a panel of expert pathologists, 17 suggesting that objective and clearly decisive biomarkers would also improve standardization and vigorous quality control of the histological diagnosis.…”
mentioning
confidence: 99%